Assessing the Role of Trust in Information Sources, Adoption of Preventive Practices, Volunteering and Degree of Training on Biological Risk Prevention, on Perceived Risk of Infection and Usage of Personal Protective Equipment Among Italian Medical Students During the SARS-CoV-2 Pandemic - Maietti, Elisa; Greco, Manfredi; Reno, Chiara; Rallo, Flavia; Trerè, Davide; Savoia, Elena; Fantini, Maria Pia; Scheier, Lawrence M.; Gori, Davide (Frontiers in Public Health, 2021)
Background: During the initial phase of the COVID-19 pandemic, the University of Bologna Medical School surveyed medical students to learn more about their preparation to confront challenges posed by the pandemic and whether it affects perceptions of viral infection risk. This information could help design risk-reduction interventions with training to mitigate possible viral exposure. Method: A cross-sectional online survey examining students’ characteristics, volunteer status, adoption of evidence-based preventive measures, trust in information sources used, infectious disease training, and knowledge of PPE usage in relation to perceived risk of infection from SARS-CoV-2 in daily living, academic, and healthcare activities. A multivariate path model estimated the simultaneous influences of all exogenous factors on perceived risk. A Poisson regression model assessed the same multivariate effects on knowledge of PPE usage. Results: The analysis sample included 537 respondents. Perceived risk of infection was highest in hospital activities. On average, students were able to use only four out of seven types of PPE albeit they adopted most of the evidence-based preventive measures. Adoption of preventive measures was positively associated with perceived risk of COVID infection. Conversely, training on PPE usage and volunteer work were associated with lower perceived risk in healthcare setting and higher PPE knowledge. Conclusion: Implementing early safety-based educational programs remedy students’ lack of knowledge in infectious disease prevention and mitigate their risk of infection. Voluntary work should be encouraged with potential benefit for both their continued medical training and strengthening the healthcare system’s response to public health emergencies.